First, distribute the 3 on the right side of the equation:
5x + 8 = 3x - 6
Next, move the variables to one side:
5x - 3x = -6 - 8
2x = -14
Finally, solve for x:
x = -14 / 2
x = -7
To check the solution, substitute x = -7 back into the original equation:
5(-7) + 8 = 3(-7) - 2
-35 + 8 = -21 - 2
-27 = -23
Both sides are not equal, so x = -7 is not the correct solution. Let's reevaluate the equation:
5x + 8 = 3(x - 2)
5x + 8 = 3x - 6
5x - 3x = -6 - 8
2x = -14
x = -14 / 2
x = -7
The correct solution for x is x = -7. The error might have been made during the checking process. Let's recheck the solution:
5(-7) + 8 = 3(-7 - 2)
-35 + 8 = 3(-9)
-27 = -27
Therefore, x = -7 is the correct solution.
solve the following equation
5x + 8 = 3 (x - 2)
show your work including your checked solution
1 answer